Unusual cause for intestinal perforation in juvenile dermatomyositis. Issue 8 (22nd August 2019) - Bhaskaran, Harikrishnan; Balan, Suma
Abstract : We report a case of juvenile dermatomyositis (JDM) with cytomegalovirus (CMV) colitis which was further complicated with perforation. The patient, a 6-year-old girl, was diagnosed with JDM 1 month prior to the current presentation. After 2 weeks of optimising her treatment with steroid, intravenous Ig and methotrexate, she was readmitted with diffuse abdominal pain. Erect abdominal X-ray revealed gas under diaphragm. An exploratory laparotomy showed perforation of the large intestine. A biopsy showed inclusion bodies of CMV with immunohistochemistry for CMV positive. Strong positive CMV DNA PCR from tissue specimen, positive IgG CMV and negative IgM CMV in blood suggested a reactivation of CMV. The treatment followed included surgery and strategic use of antiviral agents as well as immunomodulators. CMV enteritis with complications should also be suspected in optimally treated autoimmune disease patients, including JDM, when they present with abdominal symptoms.